Induksi Kalus Krisan (Chrysanthemum morifolium Ramat.) dengan Penambahan Berbagai Kombinasi Zat Pengatur Tumbuh (ZPT) - Tia Setiawati; Alma Ayalla; Anandira Witri (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2019)
Chrysanthemum is an ornamental plant that contains many secondary metabolites such as flavonoids and various volatile compounds that have the potential as medicinal ingredients. Production of secondary metabolites from plants can be carried out in vitro through callus culture. The purpose of this study was to determine the effect of Plant Growth Regulators (PGR) combination on callus formation from explants of leaves and stems of Chrysanthemum plantlets in Murashige & Skoog (MS) media. The study was conducted using a Completely Randomized Design (CRD) with a single factor in the form of 10 combinations of 2,4-D + kinetin for callus induction from stem explants and 12 combinations of NAA + BAP for callus induction from leaf explants. Observations were conducted on two months after planting. Observation data were analyzed descriptively. The results showed that callus formation occurred both from stem and leaf explants in all treatment combinations.In the group of stem explant, a combination of 3 `ppm 2,4-D + 2 ppm kinetin resulted in the highest average of callus size, wet weight, and dry weight, ie 13 (clay models); 1.186 grams; 0.316 grams respectively with a compact texture and light green, brownish dark green.Pada kelompok ekpslan daun, kombinasi 1 ppm NAA + 1 ppm BAP rata-rata ukuran, berat basah dan berat kering kalus tertinggi berturut-turut sebesar 17 (skala clay models); 1,3921 gram dan 0,1024 gram dengan tekstur kompak dan berwarna hijau muda.In the leaf explant group, a combination of 1 ppm NAA + 1 ppm BAP, the highest average of size, fresh weight and dry weight of callus at 17 (clay models); 1,3921 grams and 0.1024 grams with compact texture and light green color. Keywords: Chrysanthemum morifolium, calli, NAA, BAP, kinetin